Enhancing Digital Literacy and Chemistry Conceptual Understanding Through Hybrid On-Site E-Learning (HoSEL) for Students - Florida Doloksaribu; Albaiti Albaiti; Irwandi Yogo Suaka; Rival Iriansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to improve students' understanding of chemical concepts and digital literacy through Hybrid On-Site E-Learning (HoSEL) with a focus on the structure, nomenclature, and applications of organic compounds. This type of research is mixed methods. The participants consisted of 38 eleventh-grade science students from MA DDI Jayapura, divided into control and experimental groups. The participants consisted of 38 students of grade XI IPA MA DDI Jayapura who were divided into control and experimental groups. The control group followed a conventional teaching model (without HoSEL), while the experimental group was taught using the HoSEL model. The research instrument used a test given at the beginning and end of learning. The analysis of the research data used inferential statistics and the N-Gain test. The results of the analysis showed that before the implementation of HoSEL, students' understanding of chemical concepts was already at a very good level, but their digital literacy achievements were still very low (0.12). After the implementation of HoSEL, there was a significant increase in both conceptual understanding and digital literacy (p <0.001), which showed the effectiveness of the model, especially with high N-Gain on digital literacy (0.79). In addition, 85.5% of students responded positively to the use of the HoSEL model, making it a recommended approach for chemistry education, especially in the Papua region